Philosophical Understandings of the World, Human Life, and Society in Theravada and Vajrayana Buddhism: A Comparative Study in the Nepalese Context - Karki, Chakra Bahadur; Chetri, Neel Kumar (Medha: A Multidisciplinary Journal, 2026)
This paper explores the philosophical foundations of Buddhist ontology and karma in relation to social structure and transformation, with a focus on Theravada and Vajrayana traditions in Nepal. Drawing on Pali canonical sources—especially the Majjhima Nikaya and Cuḷakammavibhaṅga Sutta—the study examines how Theravada Buddhism presents karma as a moral law conditioning rebirth and social status, such as the notion that immoral deeds may lead to rebirth as a chandala (outcaste). Ontologically, Theravada asserts that existence is a causal process devoid of a permanent self, and liberation is achieved through ethical conduct, meditative discipline, and insight into the impermanence and non-self of phenomena. In contrast, Vajrayana Buddhism, as developed in Nepal’s Newar Buddhist tradition, elaborates a non-dual ontology grounded in śunyata (emptiness) and tathagatagarbha (Buddha-nature), where karma is not only a moral force but also a transmutable energy accessible through tantric ritual and meditative techniques. By relating these philosophical frameworks to Nepali society, the article reveals how both traditions—Theravada through ethical reform and Vajrayana through ritual and symbolic integration—offer distinct but complementary approaches to individual liberation and societal transformation. The synthesis of these two strands in the Nepali context illustrates the dynamic interplay of doctrinal diversity, social practice, and philosophical depth within contemporary Buddhist thought.